Management of mild hemophilia A. (3rd October 2018) - Franchini, Massimo; Marano, Giuseppe; Pupella, Simonetta; Vaglio, Stefania; Veropalumbo, Eva; Liumbruno, Giancarlo Maria
ABSTRACT: Introduction : Congenital hemophilia A is an X-linked bleeding disorder characterized by a variable deficiency of factor VIII activity (FVIII:C). Mild hemophilia A, defined as FVIII:C levels >5 and <40% of normal, has clinical features that are distinct from those of severe hemophilia A, being spontaneous hemorrhages or recurrent joint bleeding very rare. Areas covered : This review, which also summarizes the clinical, pathogenic, and diagnostic features of mild hemophilia A, primarily covers the management of this disorder, focusing on standard, and innovative therapies. Expert opinion : The management of mild hemophilia A includes the use of desmopressin and antifibrinolytic agents for minor bleeding episodes or surgical procedures. Conversely, major bleeding, or surgery require substitutive replacement therapy with FVIII concentrates. A number of plasma-derived and recombinant FVIII concentrates are currently available on the market for the treatment of mild hemophilia A. As regard the treatment of inhibitors, that complicate the management of these patients, a number of therapeutic options are available for the treatment of bleeding episodes and inhibitor eradication.